Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2017
DOI: 10.1159/000484900
|View full text |Cite
|
Sign up to set email alerts
|

The Correlation of Serum Brain Natriuretic Peptide and Interleukin-6 with Quality of Life Using the Chronic Obstructive Pulmonary Disease Assessment Test

Abstract: Objective: The aim of this study was to determine the levels of serum pro-brain natriuretic peptide (pro-BNP) and interleukin (IL)-6 in patients with stable chronic obstructive pulmonary disease (COPD) and to correlate these markers with health-related quality of life using the COPD assessment test (CAT). Materials and Methods: Serum pro-BNP and IL-6 levels were measured in 82 patients with stable COPD. Serum pro-BNP and serum IL-6 levels, pulmonary function, and oxygen saturation (SpO2) were measur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
18
0
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 21 publications
(22 citation statements)
references
References 31 publications
(32 reference statements)
1
18
0
2
Order By: Relevance
“…The elevated levels of IL-6 and IL-8 in the serum of subjects with BNP gene rs198389, rs6668352, and rs198388 mutations in the present study indicate that these SNPs are involved in the development of inflammatory response and may contribute to COPD. Ghobadi et al [ 33 ] showed that the levels of serum IL-6 and pro-BNP increased with the severity of COPD, and the results were consistent with the results of the present study.…”
Section: Discussionsupporting
confidence: 93%
“…The elevated levels of IL-6 and IL-8 in the serum of subjects with BNP gene rs198389, rs6668352, and rs198388 mutations in the present study indicate that these SNPs are involved in the development of inflammatory response and may contribute to COPD. Ghobadi et al [ 33 ] showed that the levels of serum IL-6 and pro-BNP increased with the severity of COPD, and the results were consistent with the results of the present study.…”
Section: Discussionsupporting
confidence: 93%
“…In this way, some of the evaluated studies noticed an increase in the serum concentration of triglycerides [ 1 , 2 , 9 , 16 , 17 , 21 23 , 25 , 35 , 51 , 61 , 63 ] and cholesterol [ 2 , 9 , 16 , 23 , 27 , 29 , 35 , 51 , 61 , 63 ] in the groups fed with DIO. This change seems to be especially related to saturated fatty acid-rich [ 27 ] obesogenic diets (Table 2 ).…”
Section: Resultsmentioning
confidence: 91%
“…This inflammatory condition contributes to the development of metabolic disorders [ 1 , 35 ], such as diabetes [ 27 ]; to a decrease in lymphatic function and cutaneous hypersensitivity [ 34 ]; and to the occurrence of other diseases, such as periodontitis [ 62 ] and respiratory allergies [ 63 ]. Furthermore, the immune system can also be altered, with an improvement in this system when there is a modulation of the production of inflammatory cytokines [ 64 ].…”
Section: Resultsmentioning
confidence: 99%
“…IL-6 is an important marker of the inflammatory response. Ghobadi et al [23] found a higher level of IL-6 in the serum with a more severe COPD condition. These results indicate that IL-6 has an important role in the development of COPD.…”
Section: Discussionmentioning
confidence: 97%